Evaluation of Fire Protection System on Educational Laboratory Building of Universitas Samudra - Haikal Fajri; Wan Alamsyah; Defry Basrin; M. Ridho Pratama; Irda Yunita (Fakultas Teknik, 2023)
This research aims to evaluate fire protection system of educational laboratory building of Universitas Samudra in Langsa city. The building, containing chemical and biological materials that are susceptible to fire, should be protected carefully against potential fires. In addition, sophisticated and expensive equipment for practicum and research including the physical building material are also an additional factor to be preserved according to large investments budget provided. The building, served as practicum and research center will be reviewed from the aspect of active, passive, and management systems that refer to Indonesian standards and regulations. Field observations, data collection and interview were performed in observing the existing condition of the building using descriptive methods. To support the evaluation process, building model is carried out using Sketchup, AutoCAD and Dialux simulation in order to achieve more in-depth observations. The results of this study show that in general the building has met adequate fire protection system standards. The existing volume of the ground water tank is only sufficient for the daily operational needs of water in the laboratory building. However, this amount is not sufficient in a fire scenario. The addition of a new ground water tank and the addition of a Siamese connection to support the need for water imported from fire trucks is required. In addition, there is a need for a fire hazard management team in the building and the need for technical operational standards for the maintenance of all components.